2021
DOI: 10.1016/j.jceh.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Tyrosinemia Type 1 in Indian Children

Abstract: The objective of this study was to determine the outcome of children with tyrosinemia type 1 from India. Methods: A retrospective observational study was conducted on 11 patients diagnosed with type I tyrosinemia under our care. Age at symptoms, age at diagnosis, age at starting 2-nitro-4-trifluoromethylbenzoyl-1,3cyclohexanedione (NTBC), duration between diagnosis and initiation of NTBC, dose given, total duration of NTBC, and outcomes were noted. Results: Eleven children with a median age of 1.1 years (0.51-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(15 reference statements)
0
3
0
2
Order By: Relevance
“…Experts in this field emphasize that treatment with the drug nitisinone, also known as 2-(2-nitro-4-trifluoromethylbenzoyl) cyclohexane-1,3-dione (abbreviated as NTBC), at a dose of 1 mg/kg/day should be initiated upon suspicion of HT1, and the response to this drug is typically rapid, with clinical improvement occurring within one week [3,10]. A number of studies have demonstrated the undeniable effectiveness of this drug [11,12,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experts in this field emphasize that treatment with the drug nitisinone, also known as 2-(2-nitro-4-trifluoromethylbenzoyl) cyclohexane-1,3-dione (abbreviated as NTBC), at a dose of 1 mg/kg/day should be initiated upon suspicion of HT1, and the response to this drug is typically rapid, with clinical improvement occurring within one week [3,10]. A number of studies have demonstrated the undeniable effectiveness of this drug [11,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…Lifelong monitoring for these liver complications in HT1 patients is of utmost importance. If treatment with nitisinone and a low-tyrosine diet is effective, long-term survival can be expected [3,14]. According to data from Sniderman King L. et al, a combination treatment of nitisinone and a low-tyrosine diet resulted in over 90% survival, normal growth, improved liver function, prevention of cirrhosis, correction of renal tubular acidosis, and improvement of secondary rickets [10].…”
Section: Discussionmentioning
confidence: 99%
“…ŬƂƊƈƁƂƇſƆƟƙ ƌƂƉ I (ŧŬ-1) -ƊƟžƄƟƋƇſ ƋƉźž-Ƅƈżſ ƁźƏżƈƊƘżźƇƇƙ, ƋƉƊƂƑƂƇſƇſ ƉƈƊƍƒſƇƇƙƆ źƆƟƇƈƄƂƋƅƈƌƇƈŽƈ ƈŻƆƟƇƍ, Ɖƈż'ƙƁźƇſ Ɓ žſƎſƄƌƈƆ ƈŻƆƟƇƍ ƊſƑƈżƂƇ Ɵ ƉƈƊƍƒſƇƇƙƆ ƆſƌźŻƈƅƟƁƆƍ ƌƂƊƈƁƂƇƍ, Ɠƈ ƉƊƂƁżƈžƂƌƖ žƈ ƉſƑƟƇƄƈżƈƠ Ƈſžƈ-ƋƌźƌƇƈƋƌƟ ƟƁ ƋƍƉƍƌƇƟƆƂ ƁźƏżƈƊƘżźƇƇƙƆƂ ƇƂƊƈƄ Ɵ ƇſƊżƈżƈƠ ƋƂƋƌſƆƂ [1,5,20,21] [5,7]. ŭ 37% ƏżƈƊƂƏ, ƙƄƟ ż ƆƂƇƍƅƈƆƍ ƉſƊſƀƂƅƂ Ɗƍƃ-ƇƟżƇƟ ƍƋƄƅźžƇſƇƇƙ HT-1, żƂƇƂƄźƘƌƖ ŽſƉźƌƈƆƂ, Ɠƈ ƑźƋƌƈ ƌƊźƇƋƎƈƊƆƍƘƌƖƋƙ ż ŝŰŤ [29].…”
Section: ũżžƈżƈɗſƈƈƙunclassified
“…ŨƄƊƟƆ ŽƟƉƈƎƈƋƎźƌſƆƟƑƇƈŽƈ ƊźƏƟƌƍ ƌź źƊ-ƌſƊƟźƅƖƇƈƠ ŽƟƉſƊƌſƇƁƟƠ, ƙƄƟ ƆƈƀƍƌƖ żƂƇƂƄƇƍƌƂ Ƈź ƉƈƑźƌƄƍ ƉƊƈƐſƋƍ ƁźƏżƈƊƘżźƇƇƙ, żƟžžźƅſƇƟ ƍƋƄƅźžƇſƇƇƙ żƄƅƘƑźƘƌƖ ŽƅƈƆſƊƍƅƈƋƄƅſƊƈƁ, ƇſƎƊƈƄźƅƖƐƂƇƈƁ ƌź ƏƊƈƇƟƑƇƍ ƇƂƊƄƈżƍ ƇſžƈƋƌźƌ-ƇƟƋƌƖ [20,2428 ]. ŭ ƉźƐƟƝƇƌƟż ƟƁ HT-1 Ɗƙž żƑſƇƂƏ ƋƉƈƋƌſƊƟŽźƝ ƊƈƁżƂƌƈƄ ŽƟƉſƊƌƊƈƎƟƑƇƈƠ ƄźƊžƟƈƆƟƈ-ƉźƌƟƠ (ŝŤŦ) [3,22,25]…”
Section: ũżžƈżƈɗſƈƈƙunclassified
See 1 more Smart Citation